2001
DOI: 10.1099/0022-1317-50-11-952
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic characterisation of a novel Streptococcus anginosus antigen that induces nitric oxide synthesis by murine peritoneal exudate cells

Abstract: A novel antigen that induces nitric oxide (NO) synthesis by murine peritoneal exudate cells (PEC) was prepared from a culture supernate of Streptococcus anginosus NCTC 10713 in dialysed medium by column chromatography with DEAE-Sephacel followed by size-exclusion high performance liquid chromatography (HPLC). A chemical analysis of the S. anginosus antigen (SAA) revealed that it mainly consisted of carbohydrates (rhamnose, N-acetylglucosamine, glucose and galactose), smaller quantities of protein and a trace a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…We previously reported that SAA, a novel bioactive antigen of S. anginosus , induces NO synthesis and COX‐2 mRNA expression by murine PEC (Sasaki et al , 1995b; Sasaki et al , 2001). Therefore, it is possible that, in some cases of oral squamous cell carcinoma, S. anginosus in dental plaque could infect to oral mucosa and the infection may lead to increased rates of DNA damage by the over‐synthesis of NO and/or COX‐2, resulting in carcinogenesis of the infected tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that SAA, a novel bioactive antigen of S. anginosus , induces NO synthesis and COX‐2 mRNA expression by murine PEC (Sasaki et al , 1995b; Sasaki et al , 2001). Therefore, it is possible that, in some cases of oral squamous cell carcinoma, S. anginosus in dental plaque could infect to oral mucosa and the infection may lead to increased rates of DNA damage by the over‐synthesis of NO and/or COX‐2, resulting in carcinogenesis of the infected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported a novel bioactive antigen (SAA) that induces NO synthesis by murine peritoneal exudate cells (PEC) from a culture supernatant of S. anginosus (Sasaki et al , 2001). Furthermore, SAA induced cyclooxygenase‐2 (COX‐2) mRNA expression by PEC (Sasaki et al , 1995b), the overexpression of which has also been observed in cancer tissues (Zang et al , 1998; Doi et al , 1999; Marrogi et al , 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Streptococcus anginosus, one of the oral streptococci, is considered a common commensal organism found in the human oral cavity. However, this organism has become known as an important pathogen in respiratory infections and subacute bacterial endocarditis (Shinzato and Saito 1995;Sasaki et al 2001;Allen et al 2002). It is also known that the presence of Strep.…”
Section: Introductionmentioning
confidence: 99%
“…According to the data of Yumoto et al ( 2001 ) , Eikenella corrodens is able to stimulate human oral epithelial cells in producing various mediators including IL-6, IL-8, and PGE2, possibly, via the secretion of soluble proteins. S. anginosus and S. mitis were observed to induce the production of in fl ammatory cytokines in human esophageal epithelial cell lines (Sasaki et al 2001 ;Narikiyo et al 2004 ) . Sugano et al ( 2003 ) detected the signi fi cant elevation in carcinogenic 8-hydroxy-deoxyguanosine (8-OHdG, resulting from the continuous generation of reactive oxygen species associated with chronic in fl ammation) in patients who tested positive for S. anginosus compared to individuals who tested negative for the bacterium.…”
mentioning
confidence: 99%